The following system of equations is _____.
y = -1/3x + 2/3
2x + 6y = 4

Question

Asked 5/7/2015 5:41:04 PM

Updated 5/8/2015 3:00:00 AM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [5/8/2015 3:00:00 AM]

s

biank1989|Points 238|

(3x - 1)^2 = 5

3x - 1 = 5^1/2

3x = 5^1/2 + 1

x = (5^1/2)/3 + 1/3

Question

Asked 5/7/2015 5:41:04 PM

Updated 5/8/2015 3:00:00 AM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [5/8/2015 3:00:00 AM]

Rating

3

x - y = 4

x + y = 2

adding up equations the result is 2x = 6

x = 6/2 = 3

3 - y = 4

y = 3 - 4 = -1

the solution for the system x - y = 4 x + y = 2 is (3, -1)

x + y = 2

adding up equations the result is 2x = 6

x = 6/2 = 3

3 - y = 4

y = 3 - 4 = -1

the solution for the system x - y = 4 x + y = 2 is (3, -1)

Added 5/8/2015 2:54:53 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [5/8/2015 10:21:08 AM]

3

y = 2x + 3

2y = 4x + 6

substitute y in the second equation the result is:

2(2x + 3) = 4x + 6

4x + 6 = 4x + 6

4x - 4x = 6 - 6

0 = 0

the system of equations y = 2x + 3 2y = 4x + 6 has infinite solutions.

2y = 4x + 6

substitute y in the second equation the result is:

2(2x + 3) = 4x + 6

4x + 6 = 4x + 6

4x - 4x = 6 - 6

0 = 0

the system of equations y = 2x + 3 2y = 4x + 6 has infinite solutions.

Added 5/8/2015 2:56:06 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [5/8/2015 10:23:40 AM]

3

For the system 3x + y = 1 y + 4 = 5x, use the second equation to make a substitution for y in the first equation, the resulting equation is 3x + (5x - 4) = 1.

Added 5/8/2015 2:58:26 AM

This answer has been confirmed as correct and helpful.

3

For the following system, x + 5y - 10 = 0 x = 2y - 8, use the second equation to make a substitution for x in the first equation. The resulting equation is: 2y - 8 + 5y - 10 = 0, it is 7y - 18 = 0 in simplest form.

Added 5/8/2015 2:59:53 AM

This answer has been confirmed as correct and helpful.

x + y = 0
x - y + 2 = 0 User: Solve the following system of equations graphically.
y - 4 = 0
2x - y - 2 = 0
What is the solution set? **Weegy:** |2x - 5| = 4 2x - 5 = -4 or 2x - 5 = 4 2x - 5 = -4; 2x = -4 + 5; 2x = 1; x = 1/2; 2x - 5 = 4; 2x = 4 + 5; 2x = 9; x = 9/2; x = 1/2 or x = 9/2 **User:** Given the following system of equations, identify the type of system.
x + y = 4
x - y = 6 **User:** Given the following system of equations, identify the type of system.
y = -x + 4
2x + 2y = 8 **Weegy:** The answer is A.independent. **User:** Which of the following points is a solution of the system shown?
x + y 6
x 4 (More)

Question

Updated 5/14/2015 3:05:31 AM

4 Answers/Comments

x + y = 0

x - y + 2 = 0

adding up equations the result is:

2x + 2 = 0

2x = -2

x = -2/2 = -1

y = -x = -(-1) = 1

The solution for the system x + y = 0 x - y + 2 = 0 is (-1, 1)

x - y + 2 = 0

adding up equations the result is:

2x + 2 = 0

2x = -2

x = -2/2 = -1

y = -x = -(-1) = 1

The solution for the system x + y = 0 x - y + 2 = 0 is (-1, 1)

Added 5/14/2015 3:02:14 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/14/2015 5:15:16 AM]

y - 4 = 0

y = 4;

2x - (4) - 2 = 0

2x = 6

x = 6/2 = 3

the solution for the system y - 4 = 0 2x - y - 2 = 0 is (3, 4)

y = 4;

2x - (4) - 2 = 0

2x = 6

x = 6/2 = 3

the solution for the system y - 4 = 0 2x - y - 2 = 0 is (3, 4)

Added 5/14/2015 3:03:27 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/14/2015 5:15:26 AM]

31,899,444

questions answered

There are no comments.